Development of RPS using a STEAM Learning Approach in the Wood Work Practice Course Building Engineering Education Program - Dharma, Adhadian Bhakti; Abdullah, Rijal; Prima, Fani Keprila (Universitas Negeri Padang, 2023)
In the Wood Work Practice and RPS lectures used in the Building Engineering Education study program, several discrepancies were found between the RPS and the current Wood Work Practice lectures. In this research the researcher wants to reveal the procedure for developing the Wood Work Practice RPS which is in accordance with the STEAM learning approach in the Department Civil Engineering, Faculty of Engineering, Padang State University. And reveals the level of validity of the development of RPS using the STEAM learning approach in the Wood Work Practice course In the Faculty of Engineering at Padang State University, within the Department of Civil Engineering, the approach employed for this study falls under the category of Research and Development. The development model used is DDD-E consisting of Decide, Design, Development, Evaluation. The research results revealed that the RPS assessment of 6 expert lecturers in the Wood Work Practice course was in the good category with a validation value of 0.86, because this value had exceeded the minimum limit of validity value, namely 0.4, this value was obtained from finding the average of the lecturers' assessments. using the Aiken V formula, these results fall into the practical category. So this RPS is suitable for use in Woodworking Practices.